Ever Ancient, Ever New. Caritas in Veritate and Catholic Social Doctrine - Williams LC, Thomas D. (Alpha Omega, 2010)
The article analyzes Pope Benedict XVI’s social encyclical Caritas in Veritate and its original contribution to Catholic social doctrine. The author begins by examining Benedict’s claim that Populorum Progressio deserves to be considered the Rerum Novarum of the present age, and asserts that the substance of this claim is not Paul VI’s specific evaluation of the social question but rather his elevation of “integral human development” as the overarching principle of Catholic social doctrine. The article goes on to explicate Benedict’s understanding of “charity in truth” as the most suitable virtue for engaging in Catholic social ethics, underscoring five ways in which charity and truth complement one another. The essay concludes with a study of the requirements of integral human development as presented in Caritas in Veritate, with special emphasis given to the three most original components of this development as proposed by Benedict: respect for human life, religious liberty and environmental responsibility.